Whole abdomen irradiation in epithelial ovarian cancer – state of the art - Gocheva, Lilia (Contemporary Oncology/Współczesna Onkologia, 2009)
Epithelial ovarian cancer (OC) as a malignancy which poses multiple challenges has led to growing attention and concern during recent years. The not very noteworthy treatment results achieved during the last three decades with contemporary chemotherapeutic schemes have led to the need for research and development of new therapeutic approaches, as well as to a resurgence of interest in radiotherapy (RT) as part of a combined modality approach and as salvage therapy for patients with small volume persistent disease after primary cytoreductive surgery and chemotherapy. This article reviews the state of the art of whole abdomen irradiation (WAI) (excluding the moving strip field technique) as part of the complex treatment of epithelial OC. The prognostic factors and risk groups of epithelial OC are discussed as indicators for WAI, giving in detail the applied treatment modalities, fractionation and total doses. Toxicity and second primary malignancies following WAI are analyzed. The clinical experience accumulated during the last decades, as adjuvant, consolidative, salvage and palliative WAI in combined treatment of epithelial OC, is presented. Current issues in the radiotherapeutic management are discussed along with ideas for future clinical research directions.